Relevance of Diabetic Retinopathy with AGEs and Carotenoid Levels Assessed by Skin Sensors - Junichi Sasaki; Yuji Takayanagi; Yoichi Kadoh; Masaki Tanito (MDPI AG, 2022)
Advanced glycation end products (AGEs) and carotenoids, the major prooxidants and antioxidants in vivo, respectively, are thought to be associated with diabetes mellitus (DM). To estimate AGEs and carotenoid levels simultaneously in patients with DM, we used noninvasive fingertip skin sensors. The study population included 249 eyes of 249 Japanese subjects (130 men, 119 women; mean age ± standard deviation, 69.9 ± 12.0 years). Ninety-three patients had DM, which included diabetic retinopathy (DR) (n = 44) and no DR (NDR) (n = 49), and 156 controls. Compared to the controls (0.44 ± 0.07 arbitrary unit (A.U.)), the AGEs scores were significantly higher in DM (0.47 ± 0.09, p = 0.029) and DR (0.49 ± 0.08, p = 0.0006) patients; no difference was seen between NDR (0.45 ± 0.09, p = 0.83) and controls. Multivariate analyses indicated that a higher AGEs level is a risk factor for DR (r = 0.030, p = 0.0025). However, the carotenoid scores did not differ in any comparisons between the controls (327.7 ± 137.0 O.D.) and patients with DM (324.7 ± 126.4, p = 0.86), NDR (320.4 ± 123.6, p = 0.93), or DR (329.4 ± 130.8, p = 0.93). The carotenoid scores correlated negatively with the AGEs scores (r = −0.21, p = 0.0007), and reflected the Veggie intake score (p < 0.0001). In patients with DM, estimations of AGEs and carotenoid levels using skin sensors can be useful for assessing their risk of DR and vegetable intake, respectively.